PENGGUNAAN FAKTOR PRODUKSI TENAGA KERJA USAHATANI CABE MERAH (CAPSINUM ANNUM L) DI KAMPUNG BUMI RAYA DISTRIK NABIRE BARAT KABUPATEN NABIRE - Sairdama, Syusantie S.; Matakena, Simon; Agapa, Selpina; Indahyani, Eni (Fakultas Pertanian dan Peternakan, 2024)
The aim of this research is to find out the productivity of red chili farming and how much labor production factors are used in each process of red chili farming in Kampung Bumi Raya, West Nabire District, this research area, determined purposively based on the consideration that at the research location there are quite a lot of farmers cultivating horticultural crops including red chili farming and the research object is farmers who operate red chili farming with an area ranging from 0.25 - 1 ha and more. from three years of red chili farming. Sampling was carried out using purposive sampling, namely taking samples deliberately, namely a sample size of 30 respondents. There were 2 (two) data collections in this study, namely primary data and secondary data. Primary data was obtained from interviews and a list of questions/questionnaires distributed to respondents. Meanwhile, secondary data was obtained from literature studies and from related agencies. From the research it was concluded that: The productivity of the red chili business was 2,062.92 Kg/Ha. Obtained from the conversion results, the average production of red chili farmer respondents at the research location was 783.53 Kg with an average land area of ​​0.38 Ha and labor productivity of 104.66 HOK. This was obtained from the average use/deployment of labor production factors for red chili farmer respondents at the research location of 39.77 HOK, divided into cleaning and bed making activities of 9.57 Ha, planting of 4.47 Ha. HOK, maintenance (replanting, fertilizer and pesticides) is 8.07 HOK, and harvest is 17.67 HOK. Suggestions that can be given include; For farmers, utilizing labor within the farming family is very important in order to reduce labor costs, and can increase production by expanding farming land. For the government to support farmers in the policies they take, and can be used as a reference for other researchers whose topics are relevant to this research, as well as in-depth analysis of the allocation of agricultural labor.